Neurotoxic β-amyloid oligomers cause mitochondrial dysfunction—the trigger for PANoptosis in neurons - Meng, Xiangyuan; Song, Qi; Liu, Zinan; Liu, Xinpeng; Wang, Yujie; Liu, Jinyu (Frontiers in Aging Neuroscience, 2024)
As the global population ages, the incidence of elderly patients with dementia, represented by Alzheimer's disease (AD), will continue to increase. Previous studies have suggested that β-amyloid protein (Aβ) deposition is a key factor leading to AD. However, the clinical efficacy of treating AD with anti-Aβ protein antibodies is not satisfactory, suggesting that Aβ amyloidosis may be a pathological change rather than a key factor leading to AD. Identification of the causes of AD and development of corresponding prevention and treatment strategies is an important goal of current research. Following the discovery of soluble oligomeric forms of Aβ (AβO) in 1998, scientists began to focus on the neurotoxicity of AβOs. As an endogenous neurotoxin, the active growth of AβOs can lead to neuronal death, which is believed to occur before plaque formation, suggesting that AβOs are the key factors leading to AD. PANoptosis, a newly proposed concept of cell death that includes known modes of pyroptosis, apoptosis, and necroptosis, is a form of cell death regulated by the PANoptosome complex. Neuronal survival depends on proper mitochondrial function. Under conditions of AβO interference, mitochondrial dysfunction occurs, releasing lethal contents as potential upstream effectors of the PANoptosome. Considering the critical role of neurons in cognitive function and the development of AD as well as the regulatory role of mitochondrial function in neuronal survival, investigation of the potential mechanisms leading to neuronal PANoptosis is crucial. This review describes the disruption of neuronal mitochondrial function by AβOs and elucidates how AβOs may activate neuronal PANoptosis by causing mitochondrial dysfunction during the development of AD, providing guidance for the development of targeted neuronal treatment strategies.